The future for follow-up of gynaecological cancer in Europe. Summary of available data and overview of ongoing trials. (March 2017) - Leeson, S.C.; Beaver, K.; Ezendam, N.P.M.; Mačuks, R.; Martin-Hirsch, P.L.; Miles, T.; Jeppesen, M.M.; Jensen, P.T.; Zola, P.
Highlights: Follow-up for gynaecological cancer is not supported by good quality evidence. Current relevant research in Europe is reviewed. Strategies using best evidence are discussed. Abstract: After completing treatment, most patients follow a pre-determined schedule of regular hospital outpatient appointments, which includes clinical examinations, consultations and routine tests. After several years of surveillance, patients are transferred back to primary care. However, there is limited evidence to support the effectiveness and efficiency of this approach. This paper examines the current rationale and evidence base for hospital-based follow-up after treatment for gynaecological cancer. We investigate what alternative models of care have been formally evaluated and what research is currently in progress in Europe, in order to make tentative recommendations for a model of follow-up. The evidence base for traditional hospital based follow-up is limited. Alternative models have been reported for other cancer types but there are few evaluations of alternative approaches for gynaecological cancers. We identified five ongoing European studies; four were focused on endometrial cancer patients and one feasibility study included all gynaecological cancers. Only one study had reached the reporting stage. Alternative models included nurse-led telephone follow-up and comparisons of more intensive versus less intensive regimes. Outcomes included survival, quality of life, psychological morbidity, patient satisfaction and cost effectiveness of service. More work is needed on alternative strategies for all gynaecological cancer types. New models will be likely to include risk stratification with early discharge from secondary care for early stage disease with fast track access to specialist services for suspected cancer recurrence or other problems.